The method of training in productive professional activity - Mena-Lorenzo, Jorge Luís; Mena-Lorenzo, Juan Alberto (Revista Portuguesa de Pedagogia, 2019)
In this study, the method of training in productive professional activity is based on educator-student cooperation as an essential way to boost relations between the educational institution and the company. We analyze how the learning of future professionals are produced and their role once inserted in the productive institutions, to establish the relationships between the didactic components of the teaching-learning process that takes place in companies